The prevalence of vertebral fractures in diffuse idiopathic skeletal hyperostosis and ankylosing spondylitis: A systematic review and meta-analysis - Netanja I. Harlianto, BSc; Solaiman Ezzafzafi, BSc; Wouter Foppen, MD, PhD; Jonneke S. Kuperus, MD, PhD; Irene E. van der Horst-Bruinsma, MD, PhD; Pim A. de Jong, MD, PhD; Jorrit-Jan Verlaan, MD, PhD (North American Spine Society Journal, 2024)
Background: Subjects with ankylosing spinal disorders, including diffuse idiopathic skeletal hyperostosis (DISH) and ankylosing spondylitis (AS) are more prone to vertebral fractures and frequently present with neurological deficit compared to the patients without an ankylosed spine. Moreover, prevalent vertebral fractures are an important predictor for subsequent fracture risk. However, the pooled fracture prevalence for DISH is unknown and less recent for AS. We aimed to systematically investigate the prevalence and risk of vertebral fractures in DISH and AS populations. Methods: Publications in Medline and EMBASE were searched from January 1980 until July 2023 for cohort studies reporting vertebral fractures in AS and DISH. Data on prevalence were pooled with random effects modeling after double arcsine transformation. Heterogeneity was assessed with I2 statistics and we performed subgroup analysis and meta-regression to explore sources of heterogeneity. Results: We included 7 studies on DISH (n = 1,193, total fractures = 231) with a pooled vertebral fracture prevalence of 22.6% (95%CI: 13.4%–33.4%). For AS, 26 studies were included (n = 2,875, total fractures = 460) with a pooled vertebral fracture prevalence of 15.2% (95%CI: 11.6%–19.1%). In general, fracture prevalence for AS remained similar for several study-level and clinically relevant characteristics, including study design, diagnostic criteria, spine level, and patient characteristics in subgroup analysis. AS publications from 2010 to 2020 showed higher fracture prevalence compared to 1990 to 2010 (18.6% vs. 11.6%). Fractures in DISH were most common at the thoracolumbar junction, whereas for AS, the most common location was the mid-thoracic spine. Conclusions: Vertebral fractures are prevalent in AS and DISH populations. Differences in fracture distribution along the spinal axis exist between the 2 disorders. Additional longitudinal studies are needed for incident fracture assessment in patients with ankylosing spinal disorders.